Analisis Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah Kota Gorontalo Boby Rantow Payu - Payu, Boby Rantow (Jurnal Akuntansi, 2014)
This Study Aims To Determine The Contribution Of Each Type Of Local Taxes To The City Of Gorontalo Local Revenues During 2007-2012.